Mimickers of neuropsychiatric manifestations in systemic lupus erythematosus. Issue 5 (October 2018) - de Amorim, Jaqueline Cristina; Torricelli, Aline Kuhl; Frittoli, Renan Bazuco; Lapa, Aline Tamires; Dertkigil, Sergio San Juan; Reis, Fabiano; Costallat, Lilian TL.; França Junior, Marcondes Cavalcante; Appenzeller, Simone
Abstract: Systemic lupus erythematosus (SLE), presenting with new onset or worsening neuropsychiatric (NP) symptoms, is a challenge in clinical practice. Mimickers such as infections, drug-induced side effects, metabolic abnormalities, malignancies, and alcohol-related disorders have to be excluded, before attributing the manifestations to disease activity. Proper diagnosis is essential to guide adequate management and reduce morbidity and mortality. In this review article, we will highlight clinical, laboratorial, and neuroradiological features that are helpful to assist in the differential diagnosis.